Exploiting the interface between philosophy and psychiatry - Bebbington, P; Broome, MR (2004)
The topics covered in this issue of the International Review of Psychiatry reflect the importance of the interface between psychiatry and philosophy. This is particularly so at a time when the very matter of psychiatry is in debate, following the development of a coherent cognitive neuroscience. Issues include the nature of explanation of mental contents defined by intentionality. Attempts to define delusion reveal the need for clear thinking across the psychiatry-philosophy boundary. Philosophical analysis is similarly required in assessing the relationship between emotion and psychopathology. Finally, the changes seen in mental illness have implications for moral philosophy, in particular for moral accountability.